Perception of development / edited by Sandra Wallman - "Wallman , Sandra (ed.)" (London, 1977)
This volume is offered as an exploration, not an argument. It is an exploration of a theme which, although obvious, has been largely neglected. There were everywhere indications that the equation of progress with material advance was rooted in specific contexts of setting and was not readily transposed into others. It was also evident that development issues had to be simplified to fit any one development model and that Occam's Razor most commonly excised the less quantifiable variables.
Keywords: Psychology